2006
DOI: 10.1523/jneurosci.0289-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Knock-Out Mice to Determine the Role of HPC-1/Syntaxin 1A in Expressing Synaptic Plasticity

Abstract: The protein HPC-1/syntaxin 1A is abundantly expressed in neurons and localized in the neuronal plasma membrane. It forms a complex with SNAP-25 (25 kDa synaptosomal-associated protein) and VAMP-2 (vesicle-associated membrane protein)/synaptobrevin called SNARE (a soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor) complex, which is considered essential for synaptic vesicle exocytosis; thus, HPC-1/syntaxin 1A is considered crucial for synaptic transmission. To examine the physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(159 citation statements)
references
References 59 publications
7
142
1
1
Order By: Relevance
“…The mice were kept under a 12 h light/dark cycle (lights on at 6:00 A.M.), and food and water were available ad libitum. STX1A Ϫ/Ϫ mice were generated as previously described (Fujiwara et al, 2006). Most of the experiments were performed using littermate WT and STX1A…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were kept under a 12 h light/dark cycle (lights on at 6:00 A.M.), and food and water were available ad libitum. STX1A Ϫ/Ϫ mice were generated as previously described (Fujiwara et al, 2006). Most of the experiments were performed using littermate WT and STX1A…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, late LTP requires the activation of adenylyl cyclase and PKA (Nguyen and Kandel, 1997;Otmakhova et al, 2000). We previously reported that HPC-1/syntaxin 1A knock-out (STX1A Ϫ/Ϫ ) mice had impaired LTP in the CA1 area of the hippocampus based on an analysis of brain slices (Fujiwara et al, 2006). Also, consolidation of contextual fear memory was im-paired.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic alteration of STX1A levels might also contribute to impaired glucose metabolism, which occurs with increased incidence in adults with WBS [23,163,164]. In cognitive functional test, Stx1a knock out mice demonstrated an increased conditioned fear memory lacking any other difference in appearance compared with control littermate [165].…”
Section: The Single Copy Gene Part Of the Wbs Regionmentioning
confidence: 99%
“…No learning and memory deficits 53,54 Impaired long-term potentiation and memory consolidation 53 N/A High embryonic lethality 54…”
Section: Baz1bmentioning
confidence: 99%
“…Single-gene knockout mouse models were also generated. [15][16][17][18] While most of heterozygous mice for each gene exhibited some relevant phenotypes, one of them (Fkbp6) showed no phenotype at all unless both alleles were knocked out, 19 suggesting that symptomatic traits could be the result of either interaction between more than one gene or the physiologic differences between mouse and human. Recently, a mouse model for WS with full hemizygous deletion has been successfully created and recapitulated most of phenotypes in human including total brain volume reduction, increased social interaction, hypersensitivity to sound and mild motor deficits.…”
mentioning
confidence: 99%